2010
DOI: 10.1007/s12374-010-9124-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Three UDP-Glucuronate Decarboxylase Genes That Are Preferentially Expressed In Gossypium Fibers From Elongation to Secondary Cell Wall Synthesis

Abstract: UDP-xylose (UDP-Xyl) is a nucleotide sugar used as substrate for producing non-cellulose materials, e. g., hemicellulose and pectic polysaccharide, in the fibers of cotton (Gossypium). Its biosynthesis is catalyzed from UDP-glucuronic acid (UDP-GlcA) by UDP-glucuronate decarboxylase (UXS). Here, we first cloned GhUXS1 in Gossypium hirsutum and Gossypium barbadense based on a transcript-derived fragment that originated from our cDNA-AFLP transcriptome profiling in cotton. GhUXS2 and GhUXS3 were also isolated vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…At least three GhUXS genes are involved in the biosynthesis of fiber cell walls in cotton. Results from our previous reverse transcriptase-PCR analysis suggested that these genes were preferentially expressed during the different developmental stages, from elongation to secondary cell wall synthesis, with trace levels of transcripts being detected in the roots, hypocotyls, and leaves (Pan et al, 2010). Here, we confirmed that GhUXS3 encodes a cytoplasmic protein.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…At least three GhUXS genes are involved in the biosynthesis of fiber cell walls in cotton. Results from our previous reverse transcriptase-PCR analysis suggested that these genes were preferentially expressed during the different developmental stages, from elongation to secondary cell wall synthesis, with trace levels of transcripts being detected in the roots, hypocotyls, and leaves (Pan et al, 2010). Here, we confirmed that GhUXS3 encodes a cytoplasmic protein.…”
Section: Discussionsupporting
confidence: 83%
“…We previously proposed a model describing how GhUXS expression influenced fiber quality in cotton (Pan et al, 2010). UDP-XYL synthase 5 (UXS5) was down-regulated during the elongation stage in fuzzless-lintless ovules of a cotton fl mutant (Padmalatha et al, 2012).…”
Section: Speculative Function Of Ghuxs3 In Determining Cotton Fiber Qmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the targets of Class B miRNAs, the expression levels of which increased from 5 DPA and reached peak levels at 10 DPA, the expression of UXS2 was reduced from 5 to 10 DPA and subsequently up-regulated at 20 DPA ( Figure 4 ). Interestingly, UXS2 has been found to be closely correlated with UDP-xylose synthesis, a process that is critical to the development of primary walls in fiber cells (Pan et al, 2010). Thus, GhmiR164 may serve as a key regulator of fiber elongation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, UXS represents a key enzyme for partitioning glycosyl residues between the hexosyl and pentosyl residues. In addition, because of its central role in sugar nucleotide interconversion, UXS is likely ubiquitous among plants and a target for regulatory control during cell wall biosynthesis [8]. The first UXS gene was identified from Cryptococcus neoformans by bioinformatics methods [6].…”
Section: Introductionmentioning
confidence: 99%